(untitled) (Impetus, 2021)
The purpose of this document is to show one of the aspects addressed in the master’s thesis of the reference, drawing from it one of the selective categories that show how the teachers of the Educational Institutions of Cauca, Puerto Rico of Algeria and Las Brisas de Patía, 2 located in the rural area, coincide significantly in their answers about the term “Conceptions”. In most cases the answers were “I do not know”, “Maybe this is...” and similar. This situation suggests the urgent need to promote, on the part of the State and the academy, the teaching qualification regarding conceptions of disability and educational inclusion, due to the close relationship of these terms between the teaching activity and the students who present any type of physiological, psychological or cognitive disability, any of them is not a reason for discrimination, on the contrary, we must develop the search for alternatives that condition the teaching and learning processes in each situation.